Chapter 1 The Place of Dance in Plutarch’s World. Written Traces of a Physical Cultural Practice - Schlapbach, Karin (Teiresias Supplements Online, 2022)
The Place of Dance in Plutarch’s World. Written Traces of a Physical Cultural Practice